Front Matter JEMT Vol 2, No 1 (2021) - editor editor (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
Contain Cover, Redactional board, Table of content, and back side cover